Assessment of the total, stomatal, cuticular, and soil 2 year ozone budgets of an agricultural field with winter wheat and maize crops. Issue 3 (30th July 2013) - Stella, Patrick; Personne, Erwan; Lamaud, Eric; Loubet, Benjamin; Trebs, Ivonne; Cellier, Pierre
Abstract: [1] This study evaluates ozone (O3 ) deposition to an agricultural field over a period of 2 years. A two‐layer soil‐vegetation‐atmosphere‐transfer (Surfatm‐O3 ) model is used to partition the O3 flux between the soil, the cuticular, and the stomatal pathways. The comparison between measured and modeled O3 fluxes exhibited a good agreement, independently of the canopy structure and coverage and the climatic conditions, which implicitly validates the O3 flux partitioning. The total, soil, cuticular, and stomatal O3 budgets are then established from the modeling. Total ecosystem O3 deposition over the 2 year period was 87.5 kg ha −1 . Clearly, nonstomatal deposition dominates the deposition budget, especially the soil component which represented up to 50% of the total deposition. Nevertheless, the physiological and phenological differences of maize and winter wheat induced large difference in the stomatal deposition budgets of these two crops. Then, the effect of simplified parameterizations for soil and cuticular resistances currently used in other models on the O3 budget is tested. Independently, these simplified parameterizations cause an underestimation of the O3 deposition ranging between 0% and 11.2%. However, the combination of all simplifications resulted in an underestimation of the total O3 deposition by about 20%. Finally, crop yield loss was estimated to be 1.5–4.2% for the winter wheat, whereas maize was not affected by O3 . Key Points: Total O3 deposition over the two‐year period was 87.5 kg ha‐1 Soil removal accounted for 55.1% of the total O3 removal Simplified parameterizations underestimated O3 deposition by 20%